Land and forest degradation inside protected areas in Latin America - Leisher, C.; Touval, Jerome L.; Hess, SM; Boucher, TM; Reymondin, Louis (MDPI, 2013)
Using six years of remote sensing data, we estimated land and forest degradation inside 1788 protected areas across 19 countries in Latin America. From 2004–2009, the rate of land and forest degradation increased by 250% inside the protected areas, and the land and forest degradation totaled 1,097,618 hectares. Of the protected areas in our dataset, 45% had land and forest degradation. There were relatively large variations by major habitat type, with flooded grasslands/savannas and moist broadleaf forest protected areas having the highest rates of degradation. We found no association between a country’s rate of land and forest degradation inside protected areas and Gross Domestic Product (GDP) per capita, GDP growth, or rural population density. We found significant, but weak, associations between the rate of land and forest degradation inside protected areas and a country’s protected area system funding, the size of the protected area, and one International Union for the Conservation of Nature (IUCN) management category. Our results suggest a high degree of heterogeneity in the variables impacting land and forest degradation inside protected areas in Latin America, but that the targeting of protected area investments on a continental scale is plausible.